Proceedings for the identification of provenances and progenies with wood productive potential in Pinus maximinoi - Santos, Wanderley dos [UNESP]; Cesario da Silva, Mayte Sampaio; Deniz, Larissa Delazari; Kieras, Wesllen Schuhli; Shimizu, Jarbas Yukio; Sousa, Valderes Aparecida de; Aguiar, Ananda Virginia de (Ipef-inst Pesquisas Estudos Florestais, 2018)
The aim of this work was to estimate the genetic variability in two tests P. maximonoi, in order to identify trees with productive potential for wood in the municipality Ventania, state of Parana, Brazil. A randomized complete block design was used in both tests. Two tests were composed of 63 progenies (area 1) and 77 progenies (area 2) from eight provenances, nine blocks and six plant plots, spaced 3 x 3 m. The evaluated traits were: Diameter at breast height (DBH, cm), total height (H, m) and volume (VOL, m(3). tree(-1)). Estimates of genetic parameters and the genetic gain in selection were estimated using the REML/BLUP method. Significant differences (p < 0.01) were observed between provenances in two areas. There were significant differences between progenies for traits H, DBH and VOL only for Dulce N. Colpan (Honduras) and San Jeronimo de Oaxaca (Guatemala) in area 1 and Tapiquil (Honduras) and Valle de Ageles (Honduras) (Dbh and VOL) in area 2. In the analysis between provenances, the low coefficients of genetic variation, additive heritability and medium progenies heritability, show a low genetic control for these traits. In average, P. maximinoi provenances showed good growth and volume performance in the Ventania-PR site. The provenances of P. maximinoi should be considered not only for commercial plantation but also for the establishment of seed production areas. Among the studied provenances, San Jeronimo (Mexico) had the highest volumes.
Keywords: forest species; genetic variation; improvement genetic; provenances